Students' perceptions of the effect of social media ostracism on wellbeing. (March 2017) - Smith, Rebecca; Morgan, Jessica; Monks, Claire
Abstract: Two studies were conducted to examine perceptions of online social media ostracism among school and university students in order to further test Williams' need threat model. In both studies, participants were randomly assigned to read a vignette describing either inclusion or exclusion on Facebook, they were asked to imagine that they were the target of this inclusion/exclusion, and to estimate how they would feel. In study 1 (N = 61, Mean age = 16.98), participants in the excluded condition estimated a significantly higher threat to their sense of belonging compared to their sense of self-esteem, control and meaning. Study 2 (N = 172, Mean age = 18.83) replicated and extended these findings by comparing school and University students' views of social media ostracism whilst controlling for their technological familiarity with Facebook. Both school and university students detected social media ostracism and anticipated impacts on their mood and psychological needs. Social media vignette interacted with educational institution demonstrating that university students perceived social media ostracism more negatively and social media inclusion more positively. Taken together, these findings suggest that whilst both school and university students perceive social media ostracism as psychologically painful, those in their first year at University, who are particularly reliant on online social media, may be more sensitive to the potential effects of exclusion and inclusion on this platform. Highlights: Effects of facebook ostracism among school and university students are compared. Both samples perceive facebook ostracism as psychologically painful. University students perceive facebook ostracism more negatively. University students perceive facebook inclusion more positively. University students appear more sensitive to exclusion and inclusion on this platform.